DIGITALISASI JOB SHEET PRAKTIKUM BERBASIS WEBSITE DI PENDIDIKAN VOKASI: TINJAUAN PUSTAKA SISTEMATIS (2021–2026) - Taufik Hidayat; Andrizal Andrizal; Martias Martias; Rifdarmon Rifdarmon (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Practicum is the core of competence formation in vocational education, yet learning is still largely guided by printed job sheets that present only static text and images, are inaccessible outside laboratory hours, and tend to lower student engagement. Digitalization of job sheets into website-based, interactive media is increasingly proposed as a solution; however, syntheses that map how such media are developed and evaluated in vocational settings remain scarce. This Systematic Literature Review (SLR) synthesises Scopus-indexed studies (2021–2026) on the development of digital and website-based practicum job sheets and digital worksheets (e-LKPD) in vocational and technical education, focusing on development models, validity, practicality, effectiveness, and their effect on student engagement. Following PRISMA 2020 guidelines, an initial Scopus search via Publish or Perish (PoP) version 8 was conducted; records were screened for the 2021–2026 window and topical relevance, and the core studies were retained for qualitative thematic synthesis. Author keyword co-occurrence mapping was performed in VOSviewer. This article reports the introduction, literature review, research questions, and method; results and discussion will be completed after metadata retrieval in PoP. The review is expected to clarify dominant development models (ADDIE, 4-D, Borg Gall), the measurement of media practicality (including the System Usability Scale), and the research gap regarding website-based job sheets in vocational practicum.Keywords: Digital Job Sheet; E-Worksheet; Website-Based Learning Media; Vocational Education; Practicum; Systematic Literature Review; PRISMA 2020